Perjuangan Rakyat Cirebon-Indramayu Melawan Imprialisme - Wahyu Iryana; Nina Herlina Lubis (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2018)
Attempts to write local history to the development of national history writing is very important, even expected at each campus has a study program must include the History Education courses Local History or can be Local Historiography. The research method that I use is the heuristic method historical research, criticism, interpretation and historiography. Exposure War history Kedondong or War of Cirebon to Dutch colonization and social protests of farmers in Indramayu during the Japanese occupation is one of the local history authors suppose caliber already can be called national history. Writing of local history is not only the responsibility of all academics who manages the department of History Education in Indonesia but also the relevant government policy